Incidence and associated risk factors for premature death in the Tehran Lipid and Glucose Study cohort, Iran - Ali Eslami; Seyed Sina Naghibi Irvani; Azra Ramezankhani; Nazanin Fekri; Keyvan Asadi; Fereidoun Azizi; Farzad Hadaegh (BMC, 2019)
Abstract Background The incidence and associated risk factors for premature death were investigated in a population-based cohort study in Iran. Methods A total of 7245 participants (3216 men), aged 30-70 years, were included. We conducted Cox proportional hazards models to identify the risk factors for premature death. For each risk factor, hazard ratio (HR), 95% confidence intervals (95% CI) and population attributable fraction (PAF) were calculated. Results After a median follow-up of 13.8 years, 262 premature deaths (153 in men) occurred. Underlying causes of premature deaths were cardiovascular disease (CVD) (n = 126), cancer (n = 51), road injuries (n = 15), sepsis and pneumonia (n = 9) and miscellaneous reasons (n = 61). The age-standardized incident rate of premature death was 2.35 per 1000 person years based on WHO standard population. Hypertension [HR 1.40, 95% CI (1.07-1.83)], diabetes (2.53, 1.94-3.29) and current smoking (1.58, 1.16-2.17) were significant risk factors for premature mortality; corresponding PAFs were 12.3, 22.4 and 9.2%, respectively. Overweight (body mass index (BMI): 25-29.9 kg/m2) (0.65, 0.49-0.87) and obesity (BMI ≥30 kg/m2) (0.67, 0.48-0.94) were associated with decreased premature mortality. After replacing general adiposity with central adiposity, we found no significant risk for the latter (0.92, 0.71-1.18). Moreover, when we excluded current smokers, those with prevalent cancer/cardiovascular disease and those with survival of less than 3 years, the inverse association between overweight (0.59, 0.39-0.88) and obesity (0.67, 0.43-1.04), generally remained unchanged; although, diabetes still showed a significant risk (2.62, 1.84-3.72). Conclusions Controlling three modifiable risk factors including diabetes, hypertension and smoking might potentially reduce mortality events by over 40%, and among these, prevention of diabetes should be prioritized to decrease burden of events. We didn't confirm a negative impact of overweight and obesity status on premature mortality events.